Away from China : reincorporating two Sinophone novels into Asian American literary canon - Lim, Soon Vin (Nanyang Technological University, 2019)
This thesis argues against the Sinocentric school of thought that perceives Sinophone literary production in the United States as “overseas Chinese literature”. I take issue with this problematic diasporic designation and its proponents, and maintain that when routes can be roots, Sinophone writing – composed and published upon the (migrant) authors’ arrival in their new homeland – in North America should also be acknowledged as a constitutive part of Asian American literature. I employ Shu-mei Shih’s Sinophone theory coined in 2004 to analyze the ways in which we can read Hualing Nieh Engle’s Mulberry and Peach (桑青與桃紅) (1976) and Geling Yan’s Fu Sang (扶桑) (1996) as two Asian/Sinophone American novels. Chapter One (“When Does The Tragic Song Of Wanderer End?”) draws upon a diverse range of scholarship, including theories on diaspora; Sinophone studies; cultural criticism; and Asian American literary history, in order to justify the objectives of my research, the structure of my thesis as well as my selection of authors and texts. Chapter Two (“Saving the Sinophone”) discusses the significant notion of “Claiming America” in Yan’s Fu Sang in order to foreground how Sinophone American authors have demonstrated, in their literary production, their deep local commitments to their new homeland in the United States. Chapter Three (“Holding Onto America, Even When Writing Back To China(s)”) employs Nieh’s Mulberry and Peach to explore how a Sinophone novel that narrates predominantly about Asia can still be read and by extension, recognized as an Asian American text.